(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper seeks to show that, in the Science of Logic Hegel, through the category of “subjective end”, distinguishes a purely instrumental dimension of the activity of concept. After delineating a general interpretation of the Doctrine of Concept, key aspects of the chapter dedicated of Teleology are re-constructed with the aim of detecting both the fundamental features and the limitations of this purely instrumental dimension of the concept. It is concluded that, in the chapter, it is possible to verify a ‘logic of the instrumentally activity’ and from this standpoint, to interpret the systematic position of the chapter. In addition, critical features of the Hegelian analysis are emphasized in regard to the general problem of mechanization and wear of the world and life, which projects the problem to the transit from chapter on Teleology to the Idea section.